Analyzing Low Sales of Walktoforest’s Birdwatching Service and Formulating Business Solutions Using the Pirate Metrics Framework - Kafabih, Avis (Journal of Economics and Business UBS, 2025)
This study employs a diagnostic problem-solving approach to analyze the root causes of low sales. The primary methodological tool used is the AAARRR (Awareness, Acquisition, Activation, Revenue, Retention, and Referral) Pirate Metrics framework. Unlike traditional marketing studies that rely on stated preferences, this research utilizes revealed preference data derived from Walktoforest’s internal digital analytics, including Instagram insights, Meta Ads performance, WhatsApp inquiry logs, and transaction records over a defined observation period. By mapping customer behavior across the funnel stages, the study identifies specific friction points where potential customers disengage from the decision-making process. The analysis reveals that Walktoforest’s low sales are not caused by product failure or a lack of market demand, but rather by structural inefficiencies in the customer journey. The funnel data indicates that while the brand generates substantial visibility with over 63,000 impressions, the transition from Awareness to Acquisition is low at 4%, suggesting that current content lacks sufficient relevance to trigger exploratory behavior. A critical bottleneck occurs between Activation and Revenue, where only 6% of interested users proceed to booking. This drop-off is attributed to behavioral barriers such as high uncertainty avoidance, perceived risk, and a lack of clarity regarding the experience. Conversely, the study finds that the Retention and Referral stages perform exceptionally well, with a 75% referral rate among participants, confirming that the post-experience value is high. Based on these findings, the research formulates a business solution strategy aimed at optimizing the customer conversion funnel. The proposed solutions focus on four key strategic phases: optimizing awareness through relevance-based targeting; enhancing experience clarity through visual onboarding to reduce cognitive load; implementing risk-reduction mechanisms such as beginner assurance messaging and low-friction booking options; and formalizing a post-experience retention loop to leverage organic advocacy. The study concludes that improving the adoption of niche ecotourism products requires a shift from volume-based marketing to behavior-driven funnel optimization.